TEACHING SPEAKING NARRATIVE THROUGH ANIMATED FABLE VIDEOS TO THE EIGHTH GRADERS OF MTS-ANNAMIRAH, BANGKALAN, MADURA (RETAIN, 2014)
TEACHING SPEAKING NARRATIVE THROUGH ANIMATED FABLE VIDEOS TO THE EIGHTH GRADERS OF MTS-ANNAMIRAH, BANGKALAN, MADURA ABDUS SUBUR English Education Department, Language and Art Faculty, Surabaya State University. abdus.chaidar@gmail.com Dra. Hj. Syukriah Abdullah English Education Department, Language and Art Faculty, Surabaya State University. Abstract The importance of speaking English is often set aside and is considered being the most difficult skillS among the others. Therefore, it is so crucial for the English teachers to keep trying to find ways or creativities to teach this skill. One of the easy ways is to use video in teaching students to speak English as it can give the real model of the target language. This study is an attempt to answer the three research questions -dealing with the implementation of video in teaching speaking: 1. How is the implementation of teaching speaking narrative through animated fable videos? 2. How are the students’ speaking narrative after the implementation of animated fable videos? 3. How are the students’ responses in teaching speaking narrative text through fable videos? Since this study was descriptive qualitative study, the writer would describe and analyze the existing phenomena during the study. In this case, the study was done in three meetings which took twenty seven students of the eighth grader of junior high school as the subject of the study. The place of the study was at Mts Annamirah, Bangkalan, Madura. There were three kinds of instruments used in this study, they were observation checklist, students’ speaking tasks, and questionnaire. From the findings, the writer noticed that the implementation of video mostly had the same activities although it was done in three meetings. The notes were about the analysis of teacher’s activity, students’ activity, teaching and learning process, material, and media used. At this point, the first viewing was a video entitled “Kaalu, The Thirsty Crow”, the second viewing was “Dove and The Ant”, and the last viewing was “The Foolish Fox”. In addition, the implementation of teaching speaking narrative through animated fable video helped students’ mastery on narrative text in retelling the story. This could be seen in the students’ speaking progress in each term of speaking components. Meanwhile, the result of students’ responses showed that the students were mostly interested in video viewing and agreed that video was helpful in getting the ideas to speak. Keywords: speaking narrative, animated fable videos INTRODUCTION The era of globalization and rapid advancement of technology will definitely give a great impact tothe English methodologies. Teachers will easily modify the teaching media using Internet access and computer to enhance the students learning, as it is stated by Warschauer (1998), a determinist position associates the mere presence of computers with successful language learning. In other words, technology has an extraordinary effect on learning, and simply including it will determine a more positive outcome for any activity. Learning English has also become the most dominant wayto support careers and as one of the important subjectsto pass the national exams. Studentsare obliged to master English.To master academicEnglish means to master the language skills such aslistening, writing, reading, and speaking, and the languagecomponents are Grammar, vocabulary, pronunciation, and spelling.Apart fromthe language skills, speaking ability howeverisoften set aside and considered as the most difficult skill to learn. (Brown and Yule (1983) state that learning to talk in the foreign language is often considered being one of the most difficult aspects of language learning for the teacher to help the students with. In order to speak one language like English, one should always practice it whenever and wherever possible.